Một vài phương pháp hiệu chỉnh dữ liệu bản đồ số hóa - Đức, Đặng Văn (Journal of Computer Science and Cybernetics, 2016)
This paper deals with an algorithm for the reduction of  the  numbers of the points to  represent a  digitized line and a method of processing  the spetial conficts in the line generalization  which are used to  design an integrated software for geographical information, maps and graphics database. The methods have been used in the development work of  a new software called PopMap by Vietnam IOIT for United Nations Department for Economic and Social Information and Policy Analysis (DESIPA).